2013
DOI: 10.1080/00224499.2013.843148
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Communication Between Early Adolescents and Their Dating Partners, Parents, and Best Friends

Abstract: This study assessed early adolescents' sexual communication with dating partners, parents, and best friends about six sexual health topics: condoms, birth control, STDs, HIV/AIDS, pregnancy, and abstinence/waiting. Using a school-based sample of 603 youth (ages = 12–15; 57% female; 46% Caucasian), we examined communication differences across demographic and developmental factors, tested whether communication with parents and best friends was associated with greater communication with partners, and examined ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
89
4
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 136 publications
(110 citation statements)
references
References 49 publications
11
89
4
3
Order By: Relevance
“…Numerous studies have documented the role of parental communication on teen sexual and reproductive health outcomes. 22,23 We found that girls who were comfortable talking to their mother about sexuality were more likely to use effective contraception though the same was not true for boys. These results suggest a lack of effective communication between parents and adolescent males on sexual and reproductive health issues – particularly around pregnancy prevention that results in a missed opportunity to engage young men in taking more responsibilities in pregnancy and STI prevention.…”
Section: Discussionmentioning
confidence: 79%
“…Numerous studies have documented the role of parental communication on teen sexual and reproductive health outcomes. 22,23 We found that girls who were comfortable talking to their mother about sexuality were more likely to use effective contraception though the same was not true for boys. These results suggest a lack of effective communication between parents and adolescent males on sexual and reproductive health issues – particularly around pregnancy prevention that results in a missed opportunity to engage young men in taking more responsibilities in pregnancy and STI prevention.…”
Section: Discussionmentioning
confidence: 79%
“…As many as half of teens report they have not discussed condoms or other important safer-sex topics with their partners (DiClemente, 1991; Ryan, Franzetta, Manlove, & Holcombe, 2007; Widman, Choukas-Bradley, Helms, Golin, & Prinstein, 2014). These low numbers are perhaps not surprising considering that open discussions about sex require skills in sexual assertiveness and negotiation that are not frequently modeled for youth (Brown & Witherspoon, 2002; Metts & Spitzberg, 1996).…”
mentioning
confidence: 99%
“…Lyons (2003) argues that "circumstances of an individual's life and their social context in family during childhood can increase the probability they will one day be exposed to, and infected by HIV". Open sexual communication between parents and adolescents has been identified as protective factor that reduces sexual risk behavior by delaying onset of intercourse Commendador, 2010;DiIorio, Pluhar, & Belcher, 2003;Jaccard, Dodge, & Dittus, 2002;Widman et al, 2014;Motsomi et al, 2016;Ayalew etal 2014;Edwards and Reis, 2014;Juma et al ,2015). Engaging parents in sexual education of the adolescents, improving underlying beliefs and norms, and improve the adolescent-parent communication, self-disclosure and television co-viewing and discussions are essential ( Dessie and Worku, 2015).Involvement of parents in the schools programmes on HIV /AIDS would improve the content and quality of their communications with adolescents.…”
Section: Discussionmentioning
confidence: 99%